2020
DOI: 10.1159/000509420
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Effect of Above-Label Doses of Somatostatin Analogs for the Management of Gastroenteropancreatic Neuroendocrine Tumors

Abstract: <b><i>Background:</i></b> Above-label doses of somatostatin analogs (SSAs) are increasingly utilized in the management of inoperable/metastatic gastroenteropancreatic neuroendocrine tumors (GEP-NETs), progressing on standard 4-weekly regimens. <b><i>Objective:</i></b> To evaluate the antiproliferative effect of 3-weekly SSA administration in a retrospective GEP-NET cohort. <b><i>Methods:</i></b> Patients with advanced GEP-NET, treated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 25 publications
1
23
0
Order By: Relevance
“…A recent retrospective analysis of above-label doses of octreotide LAR (30 mg/3 weeks) or LAN (120 mg/3 weeks) administered to 105 patients with advanced, progressive GEP-NETs on standard treatment included a multivariate analysis in which Ki-67 5e20% was independently associated with PFS duration (HR: 3.96 [95% CI 1.18e13.32] versus Ki-67 <3%; p Z 0.03) [16]. Our data suggest that patients with panNET and Ki-67 10% might benefit from increased SSA dose when experiencing the progressive disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent retrospective analysis of above-label doses of octreotide LAR (30 mg/3 weeks) or LAN (120 mg/3 weeks) administered to 105 patients with advanced, progressive GEP-NETs on standard treatment included a multivariate analysis in which Ki-67 5e20% was independently associated with PFS duration (HR: 3.96 [95% CI 1.18e13.32] versus Ki-67 <3%; p Z 0.03) [16]. Our data suggest that patients with panNET and Ki-67 10% might benefit from increased SSA dose when experiencing the progressive disease.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies support an increase in SSA dose to control progressive disease, including two retrospective studies of patients with progressive GEP-NETs treated with LAN or octreotide LAR at increased administered doses or reduced dosing intervals [14,16]. In addition, a prospective phase 2 study of dose escalation of LAN (180 mg every 28 days) in 32 patients with progressive thoracic or GEP-NETs reported a disease control rate of 47% at 12 months and median time to progression of 11 months [17].…”
Section: Discussionmentioning
confidence: 99%
“…Focusing specifically on pNENs, many studies have showed the SSAs’ efficacy in controlling the symptoms related to the hormone secretion of functional tumors, approximately in 50–100% of cases [ 23 , 24 ]. Similarly, several retrospective studies [ 25 , 26 , 27 , 28 , 29 ] and also a phase III randomized clinical trial [ 22 ] have clearly demonstrated the activity of SSAs in tumor growth control. The CLARINET study enrolled patients with advanced non-functioning GEP-NENs (except for two patients with gastrinoma in each group of treated and placebo arms), with a Ki-67 index < 10%, and that were indium-111 pentetreotide scan-positive.…”
Section: Introductionmentioning
confidence: 91%
“…The best results were observed in subjects with small intestine/colorectal primaries, Ki-67 below 5%, and no/ limited extrahepatic metastases. 32 In certain subjects, especially asymptomatic with small carcinoid burden and 5-HIAA levels within normal limits, initial watchful waiting might be adopted. Nonetheless, in all subjects with substantial serotonin production, it is reasonable to initiate the therapy with somatostatin analogs.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…The best results were observed in subjects with small intestine/colorectal primaries, Ki-67 below 5%, and no/limited extrahepatic metastases. 32 …”
Section: Treatmentmentioning
confidence: 99%